SUBTITLING STRATEGY AND READABILITY OF DIRECTIVE SPEECH ACT IN GENSHIN IMPACT PROLOGUE CHAPTER SUBTITLE - Noegraha, Rafy Apryan; Handoyo, Raden Pujo; Dhiyaningrum, Ambhita (CALL, 2023)
The phenomenon of gaming easily accessible online getting popular leads to the advancement not only on technological aspect of game, but also on the interaction of the game and users. Accordingly, subtitling strategy and readability of directive speech act in genshin impact prologue chapter subtitle becomes the main concerns of this study. Based on subtitling strategy by Gottlieb (1992), translation quality assessment by Nababan (2012), and directive speech act theory by Searle (1976), this study aimed to identify and analyze those aspect in video game Genshin Impact prologue chapter subtitle. The data were gathered from subtitle of prologue chapter of video game Genshin Impact. This research was conducted by using descriptive qualitative and quantitative method, also with total sampling method for answering the research questions. The results showed that there are 5 types of directive speech act that found, 7 of 10 strategies of subtitling that applied, and the readability level of the translation was readable. The study concluded that the data were utterances between the characters are explanations and introductions of the game since the data were on the prologue chapter. Then, the quality of readability in subtitle was considered readable due to most frequently used strategy was paraphrase. Keywords: translation, subtitling strategy, directive speech act, readability, genshin impact